The Attitude of The Chinese and Vietnamese Ruling Class Towards Western Astronomy From the 16th to the 18th Centuries - Anh Thuan TRUONG (Asian Studies, 2024)
From the 16th century to the 18th century, in order to realize the goal of promoting its propaganda and strengthening the influence of Christianity in China and Vietnam, Western missionaries, especially Jesuit missionaries, applied the method of “missionary academic” and “missionary bibliography” thoroughly, effectively and creatively. As a result, Western science and technology in general, and astronomy in particular, were gradually introduced into these two countries. The ruling class in China and Vietnam still had a few critical and negative reactions to such moves, but in general openness to and active acceptance of Western astronomical achievements were always the dominant attitudes of emperors, kings and mandarins in these two countries. On the basis of taking advantage of the original historical data sources and research achievements of Chinese, Vietnamese and international scholars, and at the same time combining the application of the research method of historical science along with other approaches, especially the comparative research method, this article will thoroughly analyse the attitude of the ruling class of China and Vietnam in receiving Western astronomy. This article also clarifies the main cause for the difference in the reception of Western astronomy by emperors, kings and mandarins in these two countries, thereby making a contribution to the study of the history of East-West cultural exchanges in China and Vietnam in the 16th, 17th and 18th centuries.